Cinema, cinema, cinema, more cinema please (Journal of Parents and Teachers, 2014)
Cinema is an element that can be used as a resource due to the great interest it arouses in young people; as a result, fun and education fit perfectly together. Having been used to deal with different topics, such as tolerance, equality, etc., this article proposes different playful activities on the occasion of the 74th Oscars.
Keywords: Oscars; cinema; pedagogic orientation; creativity